Raman spectra of putrescine, spermidine and spermine polyamines and their N-deuterated and N-ionized derivatives - Costa, A. M. Amorim da (2003)
The experimental and calculated Raman spectra of the N-hydrogenated and N-deuterated biogenic polyamines putrescine, spermidine and spermine and of their N-hydrogenated and N-deuterated hydrochloride salts in the 2000-3400 cm-1 spectral region (at distinct temperatures) are reported and analysed. A complete assignment of the N-H, C-H and N-D stretching modes is carried out, in the light of both steric and hydrogen-bonding interactions on the conformational behaviour of these systems.